Exploring highly efficient light conversion agents for agricultural film based on aggregation induced emission effects. Issue 47 (21st November 2016) - Qi, Yunpeng; Wang, Yongtao; Yu, Yongjiang; Liu, Zhiyong; Zhang, Yan; Qi, Yu; Zhou, Changtong
Abstract : Five compounds and their corresponding light conversion films were prepared based on AIE effects and the thermally activated delayed fluorescence (TADF) phenomenon. Abstract : Aggregation-induced emission (AIE) is a unique photo-physical phenomenon that has become an emerging and hot research area. It has a wide range of applications due to its excellent luminous properties. In this paper, five compounds and their corresponding light conversion films were prepared based on AIE effects and the thermally activated delayed fluorescence (TADF) phenomenon. Furthermore, ultraviolet conversion, dispersion and photo-physical properties such as UV-vis spectra, fluorescence spectra, and photo stability as well as the mechanical properties of the light conversion films were investigated in detail. The results reveal that triphenylacrylonitrile (TPA ) exhibits excellent photo stability and ultraviolet light conversion properties. In addition, the fluorescence emission spectrum ofTPA corresponds well with the absorption spectrum of plants in the blue-violet region. In particular, the light conversion film with addedTPA also shows enhanced mechanical properties and slightly lower visible light transmittance (3.79%) compared to PVC blank film. Based on the photo stabilities of the five compounds, it can be concluded that the electron-withdrawing cyano group can increase the photo stability ofTPA, while carbazole substituents are proved to have an uncertain effect on the rate of photo oxidation, which is attributed to the electron-donating properties of carbazole and increased molecular distortion or rigidity. Finally, it is worth mentioning that this is the first report utilizing AIE-active luminogens (AIEgens) in agricultural light conversion film.